APLIKASI TASK-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERTANYA CALON GURU PSP BAHASA INGGRIS - Kumara, Dewa Gede Agung Gana; Handayani, Nengah Dwi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
This study aimed to determine the application of task-based learning in improving the questioning ability to teacher of English Education Study Program. This type of research was classroom action research with research procedure including Initial Reflection (IR), Planning (P), Actions (A), Observation (O), Reflection (R) and Revised Planning (RP) done in two cycles. The subject of the research was the teacher candidate studentsin seventh semesterof English Education Study Program,Faculty of Teacher Training and Education,Mahasaraswati Denpasar University. The result of this research was the questioning ability of teacher candidate students increasedby Task-based learning application. From the result of preliminary test in pre cycle, it can be found that the ability of seventhsemester students of B class in constructing the question according to English grammar was still low seen from the preliminary test result of 35 students on pre cycle showing only 4 (11.42%) students who were able to achieve minimal passing grade, was 70. In cycle I, the ability of students began to increase with a total of 17 (48.57%) students have reached a minimum passing grade. In the second cycle, the students' ability in cycle II increases significantly with the total number of 32 (91.42%) students have reached the minimum mastery. The improvement of students' questioning ability by the application of task-based learning was also supported by the result of student questionnaires where 99.82% of students respond positively to the implementation of task-based learning.